A Confirmatory Factor Analysis of Digital Competence of Teachers in Eastern Economic Corridor Area under The Office of the Basic Education Commission - Lairayapong, Pimrampai; Ratanaolarn, Thanin (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The research aimed 1) to study the level of digital competence of teachers in Eastern Economic Corridor area under the Office of the Basic Education Commission 2) to validate and confirm the model of digital competence of teachers in Eastern Economic Corridor area under the Office of the Basic Education Commission. The samples were 477 teachers in Eastern Economic Corridor area under the Office of the Basic Education Commission. The instrument of this research was digital competence for teacher questionnaire. The data were analyzed by using descriptive statistics and confirmatory factor analysis (CFA). The result of the research were The result of analysis level of digital competence of teachers at a high level ( = 3.850, S.D. = 0.518), The aspects that showed the highest means were the empowering learners ( = 4.195, S.D. = 0.640), followed by the digital resources ( = 4.030, S.D. = 0.747), assessment ( = 3.869, S.D. = 0.633), facilitating learner’s digital competence ( = 3.761, S.D. = 0.815), teaching and learning ( = 3.703, S.D. = 0.689), and professional engagement ( = 3.693, S.D. = 0.551). The result of second order of the confirmatory factor analysis (CFA) aligned with the empirical data by X2 = 136.873, X2/df = 0.889, df = 154, p = 0.836, RMSEA = 0.000, RMR = 0.032, GFI = 0.975, AGFI = 0.958 and CFI = 1.000. The correlation coefficient between 0.002 to 0.596. Factor loading of variables were between 0.858 to 0.966. The factor loading is sorted in descending order of the weight which are professional engagement, teaching and learning, facilitating learner’s digital competence, assessment, empowering learners and digital resources. According to this research, administrators and related agencies can utilize information to encourage and develop digital competence for teachers.